Coeliac disease in Williams syndrome. Issue 11 (1st November 2001) - Giannotti, Aldo; Tiberio, Giovanni; Castro, Massimo; Virgilii, Fabio; Colistro, Franco; Ferretti, Francesca; Digilio, Maria Cristina; Gambarara, Manuela; Dallapiccola, Bruno
Abstract : BACKGROUND: Coeliac disease (CD) has been reported in several patients affected by chromosomal disorders, including Down syndrome (DS) and Turner syndrome (TS). CD has also been found in sporadic Williams syndrome (WS) patients. In this study, CD was evaluated in a consecutive series of patients with WS, in order to estimate if the prevalence of CD in WS patients is higher than in the general population. METHODS AND RESULTS: A consecutive series of 63 Italian patients with WS was studied by analysing the dosage of antigliadin antibodies (AGA) IgA and antiendomisium antibodies (AEA). In patients with positive AGA and AEA, small bowel biopsy was performed. The prevalence of CD in our WS population was compared with that estimated in a published series of 17 201 Italian students. Seven WS patients were found to be positive for AGA IgA and AEA. Six of them underwent small bowel biopsy, which invariably disclosed villous atrophy consistent with CD. The prevalence of CD in the present series of WS patients was 9.5% (6/63), compared to 0.54% (1/184) in the Italian students (p<0.001). CONCLUSION: The present results suggest that the prevalence of CD in WS is higher than in the general population and is comparable to that reported in DS and TS. AGA and AEA screening is recommended in patients with WS.